"I just had to be flexible and show good patience": management of interactional approaches to enact mentoring roles by peer mentors with developmental disabilities. Issue 20 (25th September 2018) - Schwartz, Ariel E.; Kramer, Jessica M.
Abstract: Purpose: Peer mentoring may be an effective approach for fostering skill development for mentors and mentees with developmental disabilities. However, little is known about how mentors with developmental disabilities perceive and enact their roles. Research questions: (1) How do young adults with developmental disabilities describe their role as a peer mentor in the context of instrumental peer mentoring? (2) How do they enact their perceived roles? Methods: Thematic analysis of semi-structured reflections completed by six mentors with developmental disabilities (ages 17–35) with multiple mentoring experiences. Results: Mentors perceived themselves as professionals with a primary role of teaching, and for some mentoring relationships, a secondary role of developing an interpersonal relationship. To enact these roles, mentors used a supportive interactional approach characterized by actions such as encouragement and sharing examples and dispositions, such as flexibility and patience. Mentors monitored mentee learning and engagement within the mentoring session and, as needed, adjusted their approach to optimize mentee learning and engagement. To successfully manage their interactional approach, mentors used supports such as peer mentoring scripts, tip sheets, and supervisors. Conclusions: While mentors reported several actions for teaching, they may benefit from training to learn approaches to facilitate more consistent development of interpersonal relationships. Implications for Rehabilitation: Peer mentoring may be an effective approach for fostering skill development for young adult mentors and mentees with developmental disabilities. In this study, young adult peer mentors with developmental disabilities perceived themselves as professionals with a primary role of teaching and a secondary role of developing an interpersonal relationship. Peer mentors used actions and dispositions that matched their perceived roles and supported mentees with developmental disabilities to engage in instrumental mentoring. With supports and training, young adults with developmental disabilities can successfully execute the complex relational and teaching tasks required of peer mentoring.